USULAN DESAIN CHECKING FIXTURE DENGAN METODE DESIGN FOR MANUFACTURING AND ASSEMBLY YANG ERGONOMIS - Setyoningsih, Hanna; Nurhidayat, Asep Endih; Murodif, Atfal (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
A work tool that don’t have ergonomic aspects can cause excessive fatigue to injury when used. As a result of excessive fatigue on workers can reduce the level of productivity and harm the company. PT. X is a manufacturing companies with make to order type of production. PT. X received a complaint from a customer who suffered a musculoskeletal muscle injury while using a checking fixture work tool. Checking fixture is a supporting component in the process of making a product that has a great influence on the quality of the product that will be optimized for its function and geometry. The study was conducted to find a checking fixture design that suits the customer's wishes. Ergonomic aspect analysis will be carried out to determine the dimensions of the dimensions in the process of making the design of the checking fixture by considering several things including the distance of the hand's reach to the locator pin, the height of the checking fixture, the standing position and the position of the grip checking fixture. Ergonomics analysis will be conducted using digital human modeling and simulation software. The design for manufacturing and assembly method is used to determine the costs required to make a checking fixture. Based on the analysis of the design, the proposal shows that there is an improvement in the work posture, which is indicated by a decrease in the PEI value from 2.73 to 1.82 so that the number of production has increased to 93 units. Based on the analysis of design for manufacturing and assembly the cost of making the checking fixture is Rp. 5,145,115,000/item. Keywords : Antropometri; Nordic Body Map; Posture Evaluation Index.ABSTRAKSebuah alat kerja yang tidak memenuhi aspek ergonomis dapat menyebabkan letih berlebih hingga cidera ketika digunakan. Akibat dari letih berlebih pada pekerja dapat menurunkan tingkat produktivitas dan merugikan perusahaan. PT. X adalah perusahaaan manufaktur dengan tipe produksi make to order. PT. X mendapat keluhan dari pelanggan yang mengalami cidera otot muskuloskeletal ketika menggunakan alat kerja checking fixture. Checking fixture merupakan satu komponen pendukung dalam proses pembuatan produk yang sangat berpengaruh besar terhadap kualitas produk yang akan dioptimalkan fungsi maupun geometrinya. Penelitian dilakukan untuk menemukan desain checking fixture yang sesuai dengan keinginan pelanggan. Analisis aspek ergonomis akan dilakukan untuk menentukan standar dimensi dalam proses pembuatan desain checking fixture dengan mempertimbangkan beberapa hal diantaranya jarak jangkauan tangan ke locator pin, tinggi checking fixture, posisi berdiri dan posisi genggaman checking fixture. Analisis ergonomi akan dilakukan menggunakan software digital human modeling and simulation. Metode design for manufacturing and assembly digunakan untuk mengetahui biaya yang diperlukan untuk membuat checking fixture. Berdasarkan analisis desain usulan menunjukkan bahwa terjadi perbaikan postur kerja yang ditunjukkan dengan menurunnya nilai PEI dari 2,73 menjadi 1,82 sehingga jumlah produksi mengalami peningkatan menjadi 93 unit. Berdasarkan analisis design for manufacturing and assembly biaya pembuatan checking fixture adalah Rp. 5.145.115.000 per unit. A work tool that don’t have ergonomic aspects can cause excessive fatigue to injury when used. As a result of excessive fatigue on workers can reduce the level of productivity and harm the company. PT. X is a manufacturing companies with make to order type of production. PT. X received a complaint from a customer who suffered a musculoskeletal muscle injury while using a checking fixture work tool. Checking fixture is a supporting component in the process of making a product that has a great influence on the quality of the product that will be optimized for its function and geometry. The study was conducted to find a checking fixture design that suits the customer's wishes. Ergonomic aspect analysis will be carried out to determine the dimensions of the dimensions in the process of making the design of the checking fixture by considering several things including the distance of the hand's reach to the locator pin, the height of the checking fixture, the standing position and the position of the grip checking fixture. Ergonomics analysis will be conducted using digital human modeling and simulation software. The design for manufacturing and assembly method is used to determine the costs required to make a checking fixture. Based on the analysis of the design, the proposal shows that there is an improvement in the work posture, which is indicated by a decrease in the PEI value from 2.73 to 1.82 so that the number of production has increased to 93 units. Based on the analysis of design for manufacturing and assembly the cost of making the checking fixture is Rp. 5,145,115,000/item.